Splenic haemangioma - A rare case report - Saritha C.; Aneela B.; Imranali Mohammed; Sandhya Anil S.; S. Chandrasekhar (Public Health Review: International Journal of Public Health Research, 2016)
Splenic haemangioma is benign neoplasm of the spleen with fewer than 100 cases reported in the literature. They may represent small, incidental lesions that can produce significant splenomegaly and predispose to splenic rupture. These tumors are rare, usually clinically silent and diagnosed accidentally. We report a case of 65 years old male with haemangioma of spleen presenting as splenomegaly which is extremely rare and deserves a mention.